Smart clothes and wearable technology - McCann, J.; ScienceDirect eBooks (Cambridge : Woodhead Publishing Ltd, 2009)
Smart clothing and wearable technology is a relatively novel and emerging area within the fashion and textile industry. Smart clothes and wearable technology is a relatively novel and emerging area of interdisciplinary research within the fashion, textile, electronics and related industries. This book provides a comprehensive review of the end-user's requirements and the technologies and materials available for the design and production of smart clothing. Part one looks at the design of smart clothing and wearable technology including the emergence of wearable computing, end-user requirements, and the design process from fibre selection to product launch. Part two examines the general requirements for merging of a range of textile structures with technology and communications for wearable technologies. Part three reviews the types of production technologies available for the development of smart clothing, including garment construction and fabric joining, and the final part discusses the application of these new technologies in smart clothing products and their presentation to consumers. Smart clothes and wearable technology is a unique and essential reference source for researchers, designers and engineers developing textiles and clothing products in this cross-disciplinary area. It will also be beneficial for those in the healthcare industry and academics researching textiles, fashion and design.
Part 1 The design of smart clothing and wearable technology: The emergence of wearable computing-- Types of smart clothes and wearable technology-- End-user based design of innovative smart clothing-- The garment design process for smart clothing: from fibre selection through to product launch-- Designing smart clothing for the body. Part 2 Materials and technologies for smart clothing: The influence of knitwear on smart wearables-- Woven structures and their impact on the function and performance of smart clothing-- Nonwovens in smart clothes and wearable technologies-- Sensors and computing systems in smart clothing-- The application of communication technologies in smart clothing-- Power supply sources for smart textiles. Part 3 Production technologies for smart clothing: Garment construction: cutting and placing of materials-- Developments in fabric joining for smart clothing-- Digital embroidery techniques for smart clothing-- Developments in digital print technology for smart textiles-- Environmental and waste issues concerning the production of smart clothes and wearable technology. Part 4 Smart clothing products: Smart clothing and wearable technology for the health and well-being market-- Smart clothing for the ageing population-- Smart clothing and disability: wearable technology for people with arthritis-- Wearable technology for the performing arts-- Branding and presentation of smart clothing products to consumers.
Jane McCann is Director of the Smart Clothes and Wearable Technologies (SCWT) Research Centre at University of Wales Newport, UK. Her research at SCWT concentrates on the application of smart and intelligent textiles for functional clothing in the areas of protective and corporate wear, performance sport and inclusive clothing design. She was the recipient of the 'Misha Black Award for Innovation in Design Education' in 2003 from the Royal College of Art. David Bryson is a Teaching Fellow in the Faculty of Arts, Design and Technology at the University of Derby, UK. His research interests include the use of scientific photography and multimedia to support learning teaching and assessment in applied science, art and design.
Elsevier
Keywords: Clothing trade -- Technological innovations; Textile fabrics -- Technological innovations; Wearable computers -- Industrial applications; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; TECHNOLOGY & ENGINEERING -- Textiles & Polymers; Clothing trade -- Technological innovations; Textile fabrics -- Technological innovations; Electronic books